Evaluation on the Effectiveness and Usability of the Developed Collaborative Interaction Management System - Salvacion Mata-Domingo (Research in Social Sciences and Technology, 2018)
A Collaborative Interaction Management System (CIMS) is a system that potentially provide some assistance to the teachers in managing the student's collaborative interaction in forum discussions. The projected main function of the CIMS is to provide tools that automatically gauge the quality of interaction as reflected in student's individual contributions so as to make it easier for the instructor to make judgments on the effectiveness of the collaborative process. This study aims to assess how effective and usable is the developed CIMS based on the evaluation of faculty and students. The descriptive research design is utilized in this study. The five-point Likert scale is used and the gathered data are statistically interpreted through the utilisation of a weighted mean. The sample population of this study is the one hundred twenty participants coming from the different universities in the area where the survey was conducted. The researcher adopted a survey instrument made by some software specialists. The bases of the instrument are some of the characteristics listed on the software quality model of ISO 9126. These are the functionality, usability and the reliability. Each of these software characteristics is described by some indicators to obtain the responses of the participants. The overall evaluation of the participants displayed the weighted mean of 4.0, thus it can be concluded that the functionality, usability and reliability of the software is very good.